AWS cloud projects Strengthen Your AWS Skills Through Practical Projects, from Websites to Advanced AI Applications - Pinto, Ivo; Santos, Pedro (Packt Publishing, Limited, 2024)
Tired of resumes that get lost in the pile? This book is your roadmap to creating an in-demand AWS portfolio that grabs attention and gets you hired. This comprehensive guide unlocks the vast potential of AWS for developers of all levels. Inside, you'll find invaluable guidance for crafting stunning websites with S3, CloudFront, and Route53. You'll build robust and scalable applications, such as recipe-sharing platforms, using DynamoDB and Elastic Load Balancing. For streamlined efficiency, the book will teach you how to develop serverless architectures with AWS Lambda and Cognito. Gradually, you'll infuse your projects with artificial intelligence by creating a photo analyzer powered by Amazon Rekognition. You'll also automate complex workflows for seamless content translation using Translate, CodePipeline, and CodeBuild. Later, you'll construct intelligent virtual assistants with Amazon Lex and Bedrock to answer web development queries. The book will also show you how to visualize your data with insightful dashboards built using Athena, Glue, and QuickSight. By the end of this book, you'll be ready to take your projects to the next level and succeed in the dynamic world of cloud computing.